CLIMATE CHANGE AND LIVELIHOODS: ADAPTATION PRACTICES BY RURAL TOURISM COMMUNITIES IN KARIMUNJAWA ISLAND - Setiawan, Budi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
The impacts of climate change have caused the changes in temperature, seasons, rainfall, sea level, storms, floods, drought, and extreme temperatures. Communities that are at the forefront to get the impacts of climate change are coastal and small island communities, one of which is tourism places. Karimunjawa is as one of areas that get the impact of the climate change. However, in a period of seven years, the development of tourism in Karimunjawa village has experienced a large increase as evidenced by the increasing number of foreign and domestic tourists. This paper aims to describe the phenomenon of adaptation and livelihood resilience in tourism-based villages on Karimunjawa Island as a socio-ecological system by applying the adaptive cycle as an exploratory diagnostic, dynamics, and direction tool of change in the socio-ecological system. This research utilizes a qualitative analysis of the livelihood adaptation strategies adopted by the informants. From the result of this study, it can be perceived that strategies to strengthen the resilience of communities, and especially the poor, must be based on a combination of the most effective measurable and increased commitment to the asset base and measures to provide better services. Therefore, local adaptation strategies are aimed at building livelihood resilience are very important because they will greatly affect the ability of communities to face the impacts of climate change. Tourism development policies in rural areas are very effective in building adaptation capacity and livelihood resilience of local communities. Local government institutions, particularly provincial governments, play an important role in fostering an enabling environment for local adaptation.